Accuracy of Guided Implant Surgery in the Partially Edentulous Jaw Using Digital impression versus Desktop Scanner and CBCT cast scan: Randomized Clinical Trial - Ali, Norhan; Tolba , Emad Mohamed; Amer, Maha (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: The aim of the study is to compare the accuracy of surgical guided implant produced by intraoral scanner, desktop scanner, and CBCT cast scan. SUBJECTS AND METHODS: A total of 63 dental implants were placed using 14 surgical guides. A total of 15 subjects, eight males and seven females (eight bilateral cases and seven unliteral cases), with mean age of 45 years (38–55 years) were included in the study. Patients were randomly divided into three groups (n = 21 each): Group 1: Surgical guide manufactured using intraoral digital impression. Group 2: Surgical guide manufactured using model cast scanning by CBCT while Group 3: Surgical guide manufactured using model cast scanning by desktop scanner the linear and angular deviations of inserted planned implants were measured. RESULTS: In the intraoral scan group, the mean angular deviation, platform 3D deviation, apical 3D deviation, and vertical deviation were 2.5°, 0.7 mm, 1.1 mm, and 0.6 mm, respectively. While in desktop scanner group, the mean angular deviation, platform 3D deviation, apical 3D deviation, and vertical deviation were 2.6°, 0.1 mm, 1.1 mm, and 1.1 mm, respectively. In the CBCT scan group, the mean angular deviation, 3D platform deviation, 3D apical deviation, and vertical deviation were 3.5°, 1.3 mm, 1.6 mm, and 1.7 mm, respectively. There is no statistically significance difference between intraoral scanner, CBCT cast scan, and desktop scanning on implant deviation that was observed. CONCLUSION: There was no statistically significance difference between intraoral scanner, CBCT cast scan, and desktop scanning on implant deviation that was observed although IOS shows better accuracy and least mean angular deviation.